Analisis Jiwa Leadership Melalui Kegiatan Ekstrakurikuler Paskibra Pada Siswa Kelas V SD Negeri Srondol Wetan 02 - F, Faiqussabila; Aura, Fisabillah; Arifah, Siti Lilik Ulya; Nuryadi, Anisha Anggi; Maelani, Dea Ananda Eka; Kiptiyah, Siti Maryatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research